2006
DOI: 10.1159/000094604
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Haemorrhage in Patients on Antithrombotics: Clinical Presentation and Determinants of Outcome in a Prospective Multicentric Study in Italian Emergency Departments

Abstract: Background: Intracranial haemorrhage (ICH) is the type of stroke associated with the highest death rate, and about 30% of ICH occurs in patients on antithrombotic treatment. This study relates clinical presentations and outcome of ICH patients on oral anticoagulant (OA) or antiplatelet (AP) therapy admitted to 33 Italian emergency departments (ED). Methods: Consecutive patients were enrolled after cranial computed tomography (CT). Primary outcome was the Modified Rankin Scale (MRS) score at 3 months of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 44 publications
3
19
1
4
Order By: Relevance
“…In addition, cessation of antithrombotic therapy during the acute phase of ICH may increase the incidence of fatal thromboembolic accidents. In contrast to previous studies [10], the statistical power of the effect of warfarin on mortality was smaller than that of antiplatelet agents. This difference is partly due to the fact that the admission INR value in warfarin users in the present study was generally low, and partly due to the fact that the effect of warfarin can be reversed suddenly using hemostatic agents.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In addition, cessation of antithrombotic therapy during the acute phase of ICH may increase the incidence of fatal thromboembolic accidents. In contrast to previous studies [10], the statistical power of the effect of warfarin on mortality was smaller than that of antiplatelet agents. This difference is partly due to the fact that the admission INR value in warfarin users in the present study was generally low, and partly due to the fact that the effect of warfarin can be reversed suddenly using hemostatic agents.…”
Section: Discussioncontrasting
confidence: 90%
“…In a study of recombinant activated factor VII in ICH, prior antiplatelet therapy was associated with hematoma growth when the growth was assessed as a categoric change, but it was not associated when the growth was assessed as absolute or percentage change [9]. In an Italian multicenter study, 3-month mortality after spontaneous ICH exceeded 50% in patients taking antiplatelet agents [10]. …”
Section: Introductionmentioning
confidence: 99%
“…12 As previously reported, our study found that arteriovenous malformations, tumors, ad aneurysms are relatively rare risk factors as causes of ICH. 13 About 27% patients were on antiplatelet therapy and 8.5% on anticoagulation therapy at admission. This proportion is quite similar to an Italian study of 241 patients with ICH, where 19.5% were on antiplatelets and 11.2% on anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is quite similar to an Italian study of 241 patients with ICH, where 19.5% were on antiplatelets and 11.2% on anticoagulants. 14 Baldi et al 13 have suggested that about 30% of ICH occurs in patients on antithrombotic therapy (antiplatelet and anticoagulant). In the latter study, 30.4% of patients on antiplatelets and 48.6% of patients on oral anticoagulants died in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…2007-08; 36:259-265 264 still seems to be underused in daily clinical practice for the treatment of this potentially life-threatening complication [4,5,37] . A broader use of PCCs in this clinical setting should be encouraged.…”
mentioning
confidence: 99%